2008
DOI: 10.1146/annurev.psych.59.103006.093716
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Selection

Abstract: We review developments in personnel selection since the previous review by Hough & Oswald (2000) in the Annual Review of Psychology. We organize the review around a taxonomic structure of possible bases for improved selection, which includes (a) better understanding of the criterion domain and criterion measurement, (b) improved measurement of existing predictor methods or constructs, (c) identification and measurement of new predictor methods or constructs, (d) improved identification of features that moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
2
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(227 citation statements)
references
References 170 publications
5
205
2
15
Order By: Relevance
“…More recent research has shown that notion to be too simple: job performance is a much more complex entity that varies with a host of tangible and intangible factors. According to Sackett and Lievens (2008) the recent trend is an emerging new view of job performance beyond a single unitary concept to a more differentiated model. We noted earlier the suggestion of Guion (2006, pp.…”
Section: Identity Of the Criterion Variablementioning
confidence: 99%
“…More recent research has shown that notion to be too simple: job performance is a much more complex entity that varies with a host of tangible and intangible factors. According to Sackett and Lievens (2008) the recent trend is an emerging new view of job performance beyond a single unitary concept to a more differentiated model. We noted earlier the suggestion of Guion (2006, pp.…”
Section: Identity Of the Criterion Variablementioning
confidence: 99%
“…Accordingly, Study 2 adheres to recent calls to go beyond selfreported and perception outcomes (Chan & Schmitt, 2004;Hausknecht et al, 2004;Sackett & Lievens, 2008 The course was advertised to students as a series of training sessions preparing students for their entrance on the job market. Main study topics included communication, teamwork, leadership, feedback, and conflict management approaches.…”
Section: Studymentioning
confidence: 99%
“…There are some articles that have reviewed the literature related to personnel selection (Robertson and Smith, 2001;Sackett and Lievens, 2008). This paper focuses on the fuzzy personnel selection problem approaches through a literature review and classification of the international journal articles from 1990 to 2014.…”
Section: Introductionmentioning
confidence: 99%